1963
DOI: 10.1002/macp.1963.020650111
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyses of polyvinyl acetals derived from polyvinyl alcohols of various tacticities

Abstract: The effect of the steric structure of the original polyvinyl alcohol on the rate of hydrolysis of polyvinyl acetal derived therefrom has been investigated. As the syndiotactic content of the original polyvinyl alcohol increased, the acetal derived therefrom became more easily hydrolyzable. Confirmation on the model compound led to the same conclusion; acetal derived from dl-type pentane-2,4-diol (corresponds to the syndiotactic portion) hydrolyzed more easily than that from the meso-type diol (corresponds to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1963
1963
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…A model reaction was investigated to facilitate further analysis of acetalized PVA NMR spectra and to observe the effect of the reaction conditions (concentrated or diluted medium). Previous studies used model alcohol compounds such as butane‐1,3‐diol, pentane‐2,4‐diol, or heptane‐2,4,6‐triol . Among those compounds, pentane‐2,4‐diol, with its two secondary alcohol functions, appears to be the most representative of a PVA unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A model reaction was investigated to facilitate further analysis of acetalized PVA NMR spectra and to observe the effect of the reaction conditions (concentrated or diluted medium). Previous studies used model alcohol compounds such as butane‐1,3‐diol, pentane‐2,4‐diol, or heptane‐2,4,6‐triol . Among those compounds, pentane‐2,4‐diol, with its two secondary alcohol functions, appears to be the most representative of a PVA unit.…”
Section: Resultsmentioning
confidence: 99%
“…Fujii et al acetalized pentane‐2,4‐diol and PVA with acetaldehyde and studied the hydrolysis reaction of the acetals formed in a mixture of 87.5% (v/v) dioxane/water at 60 °C using 0.02 mol L −1 hydrochloric acid. Results showed that acetals of isotactic diads from PVA were less prone to cleavage compared with acetals of syndiotactic diads . Shibatani et al obtained similar results by comparing the reactivity of formaldehyde with the meso ‐ and racemic diol units of heptane‐2,4,6‐triol and with the meso ‐ and racemic pentane‐2,4‐diol.…”
Section: Introductionmentioning
confidence: 88%
“…The relation between chemical reactivity and steric structure of high polymers has recently received considerable attention with the development of stereochemistry of high polymers. The rate of hydrolysis of poly(viny1 acetal) was shown to be markedly affected by the tacticity of the original poly(viny1 alcohol) (1). For poly(viny1 alcohol) and its derivatives, no data showing different chemical reactivities affected by the tacticity of the polymers had been obtained.…”
Section: Hydrolysis Of Poly(vinyl Acetate)s Of Various Tacticitiesmentioning
confidence: 96%
“…Chlorination of polymersl62-165 also yields otherwise unavailable polymers which are useful for reference purposes, provided the reactions are sufficiently mild that substitution reactions don't occur. Thus, AUFDERMARSCH and PARI-~~~1 6 2 prepared cis-polychloroprene by the following series of reactions (20) :…”
Section: Other Polymer Transformations Yielding Polywleric Modelsmentioning
confidence: 99%